Laboratory investigation of high pressure survival in Shewanella oneidensis MR-1 into the gigapascal pressure range - Hazael, Rachael; Foglia, Fabrizia; Kardzhaliyska, Liya; Daniel, Isabelle; Meersman, Filip; McMillan, Paul (Frontiers in Microbiology, 2014)
The survival of Shewanella oneidensis MR-1 at up to 1500 MPa was investigated by laboratory studies involving exposure to high pressure followed by evaluation of survivors as the number (N) of colony forming units (CFU) that could be cultured following recovery to ambient conditions. Exposing the wild type bacteria to 250 MPa resulted in only a minor (0.7 log N units) drop in survival compared with the initial concentration of 108 cells/ml. Raising the pressure to above 500 MPa caused a large reduction in the number of viable cells observed following recovery to ambient pressure. Additional pressure increase caused a further decrease in survivability, with approximately 102 CFU/ml recorded following exposure to 1000 MPa (1 GPa) and 1.5 GPa. Pressurizing samples from colonies resuscitated from survivors that had been previously exposed to high pressure resulted in substantially greater survivor counts. Experiments were carried out to examine potential interactions between pressure and temperature variables in determining bacterial survival. One generation of survivors previously exposed to 1 GPa was compared with wild type samples to investigate survival between 37°C to 8°C. The results did not reveal any coupling between acquired high pressure resistance and temperature effects on growth.